Conceiving the Indian Buddhist Patriarchs, by Stuart H. Young. (4th March 2021) - Tull, Herman
Abstract : Conceiving the Indian Buddhist Patriarchs, by Stuart H. Young. Honolulu, HI: University of Hawaii Press, 2015. ix + 338 pp., $60.00 (hb). ISBN 9780824841201.